Metode Pembayaran Elektronik yang Aman pada Online Shopping Berbasis Kriptografi Visual - Trihastuti Yuniati; Iqsyahiro Kresna A. (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Phishing and identity theft are common threats of online shopping. Phishing is an attempt to steal personal data from legitimate user. In this paper we propose a secure e-payment method using a credit card based on visual cryptography. This method adopts the existing 3D-Secure technology. Visual cryptography is applied in: user-merchant authentication, user-card provider authentication, user-card issuer authorization. It is applied to captcha image generated by merchant during registration using (2, 2) scheme with 2-subpixel expansion, to a text file containing credit card information sent by merchant to the card provider using (2, 2) scheme with pixel replacement, and to quick response code containing one-time-password that is used to authorize the payment transaction using (2, 2) scheme with 4-subpixel expansion. The test results show that out of 100 trials, all of them give 100% true positive. This indicates that the method is able to prevent phishing and identity theft, in sense of authentication, authorization, confidentiality, and integrity are gained. Phishing can be prevented because only legitimate participant who has an image share. Identity theft can be prevented because credit card details are not stored in the merchant’s database. Authorization is more guaranteed because only authenticated user can authorize the payments.